Atividades biológicas de xilana de sabugo de milho - Silveira, Raniere Fagundes de Melo (2010)
The corn cob is an agricultural by-product still little used, this in part due to the low knowledge of the biotechnological potential of their molecules. Xylan from corn cobs (XSM) is a polysaccharide present in greater quantity in the structure of plant and its biotechnology potential is little known. This study aimed to the extraction, chemical characterization and evaluation of biological activities of xylan from corn cobs. To this end, corncobs were cleaned, cut, dried and crushed, resulting in flour. This was subjected to a methodology that combines the use of alkaline conditions with waves of ultrasound. After methanol precipitation, centrifugation and drying was obtained a yield of 40% (g/g flour). Chemical analysis indicated a high percentage of polysaccharides in the sample (60%) and low contamination by protein (0.4%) and phenolic compounds (> 0.01%). Analysis of monosaccharide composition indicated the presence of xylose:glucose:arabinose:galactose:mannose:glucuronic acid in a molar ratio 50:20:15:10:2.5:2.5. The presence of xylan in the sample was confirmed by nuclear magnetic resonance (¹H and ¹³C) and infrared spectroscopy (IR). Tests were conducted to evaluate the antioxidant potential of XSM. This showed a total antioxidant capacity of 48.45 EAA/g sample. However, did not show scavenging activity of superoxide and hydroxyl radical and also reducing power. But, showing a high capacity chelating iron ions with 70% with about 2 mg/mL. The ability to XSM to influence cell proliferation in culture was also evaluated. This polymer did not influence the proliferation of normal fibroblast cells (3T3), however, decreased the rate of proliferation of tumor cells (HeLa) in a dose-dependent, reaching an inhibition of about 50% with a concentration around 2 mg/mL. Analyzing proteins related to cell death, by immunoblotting, XSM increases the amount of Bax, Bcl-2 decrease, increase cytochrome c and AIF, and reduce pro-caspase-3, indicating the induction of cell death induced apoptosis dependent and independent of caspase. XSM did not show anticoagulant activity in the PT test. However, the test of activated partial thromboplastin time (aPTT), XSM increased clotting time at about 5 times with 600 μg of sample compared with the negative control. The presence of sulfate on the XSM was discarded by agarose gel electrophoresis and IR. After carboxyl-reduction of XSM the anticoagulant activity decreased dramatically. The data of this study demonstrate that XSM has potential as antioxidant, antiproliferative and anticoagulant compound. Future studies to characterize these activities of XSM will help to increase knowledge about this molecule extracted from corn and allow their use in functional foods, pharmaceuticals and chemical industries.